Meningkatkan Hasil Belajar Siswa dengan Menggunakan Media Audio Visual dalam Pelajaran Agama Katolik Kelas 6 SD Negeri 13 Hutanamora Kecamatan Pangururan Kabupaten Samosir - Berman Manullang (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2025)
This study aims to determine the increase in students' interest in learning through the use of audio visual media in Catholic Religion lessons in grade 6 of SDN 13 Hutanamora, Pangururan District, Samosir Regency. The method used is Classroom Action Research (CAR) which is carried out in two cycles, including the planning, implementation, observation, and reflection stages. The subjects of the study consisted of 17 students, with instruments in the form of learning interest questionnaires, observation sheets, assessments, and interviews.The results of the study showed a significant increase in both interest and student learning outcomes after the use of audio visual media. The average value of the diagnostic assessment increased from 61.47 to 71.47, formative from 65 to 75, and summative from 68.24 to 78.82. Observations showed that students became more active, interested, and participatory in learning, with an increase in learning interest in the "Very" category from 47% to 94%. All dimensions of the Pancasila Student Profile also showed an increase, especially in the aspects of independence, creativity, and mutual cooperation. Student interviews support the data, where 94% of students stated that audio visual media helped understand the material and made learning more interesting. Observations during the learning process showed an increase in student discussion, enthusiasm, understanding, and interest from the first cycle to the second cycle.Thus, audio visual media has been proven effective in increasing student interest and learning outcomes, and is recommended for use as an innovative and enjoyable learning strategy.